Cairo: city of â€˜re-foundingâ€™. A survival strategy for the contemporary Mediterranean city (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The thesis’s argument finds its reasons in contexts where environmental, social and economic conditions produce landscapes at the edge of survival, ‘re-founding’ parts of the city inside unconventional cities. Cairo is a main example where entire neighbourhoods have been transformed by the huge application for survival through languages and uses completely different from currents ones. «How many cities is Cairo made?». According to J. Abu-Lughod, Cairo is made by 13 cities, each one with urban, economic and social different characteristics. The informal city is born in the 60’s. It creeps into historical fabrics recycling apparently abandoned materials and structures; it devours desert areas increasing the thickness of the existing city; it includes pre-existences or rather resistances. In particular, the study’s object which the paper wants to examine in depth is the City of the Dead, or Cairo Necropolis, discussing its ‘re-founding’ nature different from what we usually think about it.